Reduced graphene oxide preparation and its applications in solution-processed write-once-read-many-times graphene-based memory device. (November 2017) - Ooi, Poh Choon; Haniff, Muhammad Aniq Shazni Mohammad; Wee, M.F. Mohd Razip; Dee, Chang Fu; Goh, Boon Tong; Mohamed, Mohd Ambri; Majlis, Burhanuddin Yeop
Abstract: We fabricated graphene-based non-volatile memory device by solution-processed route in this work. Thermally reduced graphene oxide (rGO) on quartz substrate prepared in the ambient of acetylene/hydrogen plasma treatment was used as bottom conductive electrode to replace the commonly-used bottom conductive indium-tin-oxide layer. The morphology of the rGO film was characterized and used for device fabrication. The device was fabricated in the simple structure of silver nanowires/nanocomposite/rGO/quartz and the nanocomposite was prepared by mixing the graphene quantum dots and graphene oxide in ethanol. Current-voltage ( I – V ) measurement of the fabricated device shows current bistablity with the similar behavior as write-once-read-many-times (WORM) memory device. The ON/OFF ratio of the current bistability for the devices was as large as 1 × 10 3 with retention stability up to 1 × 10 4  s. The direct tunnelling, trapped-charge limited-current, and Ohmic conduction were proposed as dominant conduction mechanisms through the fabricated NVM devices based on the obtained I – V characteristics. Graphical abstract: